Strain Improvement Of Specialty Mushroom, Calocybe Indica, Through Mutagenesis (Applied Biological Research, 2011)
Calocybe indica, a specialty mushroom, is the third most popular  mushroom in India. During present investigation 9 strains of C. indica  were cultivated on wheat straw using the recommended technology.  Maximum biological efficiency was obtained in strain Ci-3 (81.28%). The  improvement in Ci-3, a high yielding strain, was attempted using  mutagenic treatment on protoplasts. Four mutagenic treatments (one  irradiation and three chemical) yielded 30 putative mutants. Growth  studies of putative mutants indicated maximum growth rate of CMB-4 on  wheat straw while CMN-11 gave maximum biomass on complete yeast  extract medium. Mutant CMN-9 gave maximum endoglucanase (0.345 µg  min-1 ml-1) and xylanase (0.54 µg min-1 ml-1) activity. Seven mutants were  identified on the basis of growth and enzymes studies. Cultivation of  mutants was carried out on wheat straw following hot water treatment.  Four mutants (CMN-3, CMN-9, CMN-11 and CMB-4) gave significantly  higher yield than the parent.
Keywords: Calocybe indica; enzyme activity; mushroom; mutagenesis; putative mutants; yield